REDESAIN TERMINAL PELABUHAN TANJUNG EMAS DENGAN PENDEKATAN ARSITEKTUR EKOLOGIS DI SEMARANG - Yoyok Ariyono; Musyawaroh Musyawaroh; Sri Yuliani (ARSITEKTURA, 2015)
Port of Tanjung Emas Semarang is important role as a gateway to the sea for the economy and tourism, especially in Central Java. In the decision the directors of PT. Pelabuhan Indonesia III August 5, 2002 mentions the development plan Tanjung Emas Port in Semarang and plan to build a passenger terminal building of ships. Port of Tanjung Emas Semarang also included in the program of Eco-Port so that the development process must consider environmental aspects. Redesign of the passenger ship terminal at the Port of Tanjung Emas Semarang is aimed to increase user comfort and to change the dirty and polluting image of the port terminals. The main problem of this design is how toimprove the conditions terminals to make it better and environmentally sound by applying the principles of Ecological Architecture. The method is based on the concept of Ecology Architecture with the cozy atmosphere is created by the climate-responsive design and environmentally friendly.  The result of redesign is passenger ship terminal at the Port of Tanjung Emas Semarang with appropriate Ecological Architecture concept that can be convenient for the visitors and the building can maintain harmony between architecture and surrounding environment. Keywords: Building Ecofriendly, Ecology Architecture, Passenger Ship Terminal, Redesigning